Pendidikan Karakter dan Apresiasi Seni melalui Kegiatan Angklung Tingkat TK di Nganjuk - Wathon, A (AS-SABIQUN, 2025)
This study aims to critically analyze the internal and external mechanisms that enable angklung activities in kindergartens in Nganjuk to serve as an effective catalyst for instilling character values and developing artistic appreciation in early childhood, while also identifying associated challenges and opportunities. A qualitative approach was employed using a multi-site case study design grounded in a phenomenological-interpretive lens, allowing for the exploration of subjective narratives and contextual understanding from key participants. The findings reveal that angklung activities, through their collective dynamics and the demand for musical harmony, intrinsically foster the internalization of character values such as discipline, cooperation, empathy, and responsibility—not merely through verbal instruction, but through meaningful, concrete experiences. These results reinforce theories of holistic education and child developmental psychology, while also challenging the dominance of cognitively-focused educational approaches. The implications of this study contribute to the enrichment of arts pedagogy literature rooted in local culture and early childhood character education. Practically, the study offers strategic recommendations for policymakers, particularly local governments and the Ministry of Education, to consider replicating and adapting this angklung-based arts learning model. It also opens avenues for further research on its long-term impacts and variations of implementation across diverse socio-cultural contexts.